A Comprehensive Estuarine Dissolved Organic Carbon Budget Using an Enhanced Biogeochemical Model. Issue 5 (22nd May 2020) - Clark, J. B.; Long, W.; Hood, R. R.
Abstract: Complicated biogeochemical cycling and differential organic matter reactivity make quantifying the relative contribution of a given source of organic carbon to the standing stock within an estuary difficult. Here, a new model of tidal marsh‐estuary organic carbon cycling is presented for the Rhode River, MD, a well‐studied tributary of the Chesapeake Bay, USA. A dissolved organic carbon (DOC) budget was estimated by summing the source and sink terms and the advection of water within the tributary. 13.1% and 15.3% of the total DOC input to the Rhode River entered from the marsh and the watershed, respectively, and 52.6% was derived from phytoplankton production. Extrapolating to the entire year, 35.5 Mg of DOC is exported to the main stem of Chesapeake Bay annually, which accounts for 12.3% of the total allochthonous and autochthonous inputs to the estuary. Removing the modeled marsh at the head of the Rhode River decreased export of DOC to the main stem by 39.2%, and up to 56% of the estuarine DOC standing stock can be attributed to the marsh. The model described here can be used across temperate estuarine systems and provides a new methodology for quantifying the amount of DOC that can be attributed to or lost by specific source and sink pathways. Plain Language Summary: Tidal wetlands are potentially significant in global carbon cycling, taking large quantities of carbon dioxide out of the atmosphere and fixing it as plant and root biomass. Some of this fixed carbon is buried on long time scales, but a large portion is also transported out of wetlands into estuaries. Understanding where the carbon goes and how long it takes to get there is important for carbon cycling and potentially feedbacks related to climate change. The role tidal wetlands play in estuary carbon cycling and biogeochemistry is complex, and this paper uses a computer model to give insight into how these two important systems are linked. We found that a tidal wetland in a tributary of Chesapeake Bay contributes a large portion (39%) to the total organic carbon export from the tributary. This implies that relative to their inputs, tidal wetlands potentially contribute a greater portion to the total export from estuaries. Wetlands are thus potentially more important in carbon budgets than their inputs to estuaries would suggest. Key Points: A biogeochemical model was enhanced to include six pools of dissolved organic matter and fully spectral UV‐visible light attenuation Phytoplankton production was the largest contributor to the estuarine dissolved organic carbon budget at 52.6% A tidal marsh contributed 39.2% to the export of dissolved organic carbon from a tributary of Chesapeake Bay